2008
DOI: 10.1074/jbc.m702681200
|View full text |Cite
|
Sign up to set email alerts
|

The Motor Protein Prestin Is a Bullet-shaped Molecule with Inner Cavities

Abstract: Prestin is a transmembrane motor protein localized at the outer hair cells (OHCs) of the mammalian inner ear. Voltage-dependent conformational changes in prestin generate changes in the length of OHCs. A loss of prestin function is reported to induce severe auditory deficiencies, suggesting prestin-dependent changes of OHC length may be at least a part of cochlear amplification. Here we expressed the recombinant FLAG-fused prestin proteins in Sf9 cells and purified to particles of a uniform size in EM. The squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
61
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 45 publications
(73 reference statements)
12
61
0
Order By: Relevance
“…Surprisingly, the structure described is a very open wireframelike structure, with overall volume exceeding that of much larger proteins, such as the InsP 3 receptor (1,252 kDa, vs. 383 kDa for TRPC3), and with insufficient continuous density to form an obvious transmembrane channel domain. It bears little resemblance to a structure derived from electron microscopy of TRPC3 in negative stain by the same group (38), although the latter is strikingly similar to their bullet-shaped negative-stain structures of TRPM2 (689 kDa) (39), and the unrelated membrane protein, prestin (326 kDa) (40). Based on our preliminary results with TRPV2 and TRPY1, a yeast channel related most closely to the TRPC family among mammalian channels, it seems likely that the structures of TRP channels in general follow the basic structural organization described here for TRPV1.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the structure described is a very open wireframelike structure, with overall volume exceeding that of much larger proteins, such as the InsP 3 receptor (1,252 kDa, vs. 383 kDa for TRPC3), and with insufficient continuous density to form an obvious transmembrane channel domain. It bears little resemblance to a structure derived from electron microscopy of TRPC3 in negative stain by the same group (38), although the latter is strikingly similar to their bullet-shaped negative-stain structures of TRPM2 (689 kDa) (39), and the unrelated membrane protein, prestin (326 kDa) (40). Based on our preliminary results with TRPV2 and TRPY1, a yeast channel related most closely to the TRPC family among mammalian channels, it seems likely that the structures of TRP channels in general follow the basic structural organization described here for TRPV1.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the baculovirus/Sf9 insect cell system is generally used as a high-expression system due to its well-organized and easy-to-use method, the post-translational modification pattern of prestin expressed in the Sf9 cells is considered to be different from that of native prestin. In fact, the glycosylation pattern of prestin in Sf9 cells and that in native prestin are found to differ from each other (11) (16) (17) . Since the glycosylation pattern is related to the protein stability, there is a possibility that the stability of prestin expressed in Sf9 cells is lower than that expressed in mammalian OHCs.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation using purified prestin, which would enable us to obtain signals from only prestin, is a promising approach to gain new information on prestin. Recently, it has been reported that recombinant prestin molecules were purified from Sf9 insect cells using a baculovirus expression system, and employing such molecules, it was revealed by electron microscopy that prestin is bullet-shaped (16) . However, although the baculovirus/Sf9 insect cell system is generally used as a high-expression system due to its well-organized and easy-to-use method, the post-translational modification pattern of prestin expressed in the Sf9 cells is considered to be different from that of native prestin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two significant studies on such structure have been reported. Mio et al [7] purified prestin from insect cells which were engineered to express prestin and observed purified prestin by EM. Results indicated that prestin is a bullet-shaped molecule.…”
Section: Introductionmentioning
confidence: 99%